Enhancing primary school pupils' mathematics creative ability through activity based learning approach - Bright Lhechukwu NWOKE (Universitas Malikussaleh, Aceh Utara, Indonesia, 2021)
Mathematics creativity is very important in studying mathematics at every level of education but less attention is paid to it in the teaching-learning process and this has resulted to poor performance in the subject. The study investigated how activity based learning approach can enhance the creative skills of primary school pupils. A sample of 185 pupils from six purposively selected government owned primary schools in Owerri west local Government area of Imo state was used for the study. The study was a quasi-experimental research type adopting the pre-test, posttest non equivalent control design. The instrument for data collection was a researcher made objective test titled “Mathematics Creativity Test (GAT)”Instrument which had reliability coefficient of 0.79 determined using Kuder-Richardson formula (KR21). The experiment group was taught geometric concepts using Activity-Based Learning Approach while the control group was taught using the traditional approach. The data generated was analyzed using mean and standard deviation to answer research questions while the hypotheses were tested using ANCOVA statistical tool at 0.05 level of significance. The result of the study revealed that Activity-Based Learning Approach enhanced pupils’ mathematics creative ability irrespective of gender and ability levels. Based on the result, it was recommended that Mathematics teachers at the primary school level should apply pupils centered approaches such as activity-based learning approach in teaching to enhance pupils’ creativity in mathematics.